Prevalence and predictors of infected diabetic foot ulcers (DFU) and DFU-related osteomyelitis amongst industrial workers wearing occupational safety footwear - Sunetra Mondal; Moushumi Lodh; Sambit Sahoo; Kaushik Paul; Debasis Biswas; Chaitanya Krishna; Ashok Parida; Arunangshu Ganguly; Riddhi DasGupta (Scientific Reports)
Abstract Professionals like deep-miners and factory-workers wear specialized safety-shoes to protect against occupational hazards (OF). The risk factors, clinico-microbiologic profile and complications of diabetic foot ulcers (DFU) in these professionals remain unexplored. A cross-sectional observational study was conducted to describe the unique clinico-microbiologic profile of DFU in those wearing occupational-footwear (OF) and find risk factors for DFU related osteomyelitis in them. Of 331 DFU cases seen over 5 years, those wearing OF (n = 107, 68 underground-miners and 39 steel-factory-workers) had high prevalence of forefoot-DFU (81.3%), dorsal-DFU ( 58.9%), recurrent-DFU (31.8%) and of polymicrobial infections (16.8%). Those with osteomyelitis in the OF group ( n = 53) were younger (53.3 vs. 57, p = 0.02), had higher prevalence of peripheral arterial disease (41.5% vs. 24.1%), past-amputation (28.3% vs. 11.1%), higher SINBAD scores, and were also less likely to change occupational-footwear at < = 6-month-interval (22.6% vs. 55.6%) than those without osteomyelitis (p < 0.05 for all). Increasing age, history of past amputation, CRP and reduced frequency of changing the OF were significant positive risk factors for osteomyelitis. OF change at < = 6-month-interval had a protective effect against osteomyelitis (OR : 0.21, C.I 0.07–0.54, p = 0.002) as well as for recurrence (OR : 15, C.I.: 0.04–0.46, p = 0.002) of DFU. Existing national standards for OF manufacturing and regulations regarding their use in India are inadequate and must be made more stringent for professionals with diabetes, especially those at high risk for DFU like the elderly, history of past amputation or those with LOPS. They need detailed foot-measurements for proper fit, should wear OF always at their work-place and change OF frequently for adequate against DFU-related osteomyelitis as also, recurrent DFU.